A prospective observational study on drug utilization pattern in medical intensive care unit of a tertiary medical care hospital - R., Divyashree C.; K., Nalini G.; M., Suresh R.; P., Deepak; N., Sahana G.; Nagaral, Jayashree V.; N., Mohith; V., Rakshitha B. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Drug utilization research is a part of Pharmacoepidemiology defined by the WHO as the study of marketing, distribution, prescription, and use of drugs in a society, with special emphasis on the resulting medical, social and economic consequences. Conducting periodic studies of pattern of drug use in our hospital setting is essential to critically analyse the current hospital drug policies and to make recommendations based on various guidelines to improve upon the current drug usage pattern. Aims and objectives of the study was to generate data on the drug utilization pattern in Medical ICU and to monitor antimicrobial usage in MICU. Methods: Patients who were admitted in medical ICU of Hassan institute of Medical Sciences were recruited based on inclusion-exclusion criteria. The study was conducted over a period of 3 months from April 2018 to June 2018. The demographic and clinical treatment data of patients were collected. The prescriptions were assessed as per the WHO indicators. Results: Common causes of admission were suicidal poisoning, snake bite, viral thrombocytopenia, myocardial infarction and stroke. The average duration of stay was 5.74 days and average number of drugs/patient was 5.26. Pantoprazole, Ranitidine, Ceftriaxone, Atropine, Pralidoxime, ASV, Ondansetron, and N-acetylcysteine were commonly prescribed drugs. 42.4% of drugs were prescribed by generic names and 84.2% of the drugs were prescribed from Essential Medicine List. Conclusions: This study will provide database to address prescription protocols and guide appropriate use of drugs in the ICU setting.